Osteonecrosis of the jaw (ONJ): diagnosis and management in 2015. Issue 3 (March 2016) - Khan, A.; Morrison, A.; Cheung, A.; Hashem, W.; Compston, J.
Abstract Osteonecrosis of the jaw (ONJ) has been associated with the use of aminobisphosphonates and denosumab. The vast majority (>90 %) of cases occur in the oncology patient population receiving high doses of intravenous bisphosphonates or subcutaneous denosumab. The incidence of ONJ in the osteoporosis patient population is very low and is estimated at 1–90 per 100, 000 patient-years of exposure. In the oncology patient population the incidence appears to be related to dose and duration of exposure, and prevalence has been estimated to be as high as 18.6 %. A number of risk factors in addition to antiresorptive therapy have been identified. These include the presence of periodontal disease, oral surgical procedures with extractions or implants, radiation therapy, chemotherapy, diabetes, glucocorticoid use, and smoking. Antiangiogenic agents appear to contribute to the risk of ONJ, however, data at this time are limited and further evidence is required prior to confirming a causal relationship. ONJ may be prevented with optimization of oral hygiene, the use of oral antimicrobial mouth rinses, as well as systemic antibiotic therapy. Individuals not responding to conservative management or in the advanced stages of ONJ may be considered for surgery, as data over the past several years have demonstrated surgical success in this patient population. Case reports have indicated that teriparatide may enhance healing. A number of experimental therapies are being evaluated and include the use of bone marrow stem cell intralesional transplantation, local application of platelet-derived growth factor, hyperbaric oxygen, tissue grafting, and low-level laser therapy. This paper summarizes the current research as well as the international consensus on the diagnosis and management of ONJ.